MATHEMATICAL MODEL OF UNMANNED AERIAL VEHICLE CONTROL IN SINGLE CONTROL CHANNEL - Kharchenko, Volodymyr; Мatiychyk Denys (Proceedings of National Aviation University (archive), 2017)
Objective. The main aim of this research is development of the mathematical model. Developed model will allow deeper, qualitative and faster selection of the proper values of coefficients that are necessary for optimal and effective interaction between the human and machine. Methods. In order to develop a mathematical model of unmanned aerial vehicle control in a single control channel, the classical model of aircraft control was applied. Comparative analysis of turn execution in manual and semiautomatic control modes of unmanned aerial vehicle by remote pilot was applied. Results. The mathematical model “Remote pilot – Remote Control System – Unmanned Aerial Vehicle” under change of unmanned aerial vehicle heading on horizontal plane was proposed. The model takes into account the remote pilot’s actions during airplane control, as well as of aircraft maneuverability when it is equipped with radio control and has a flight controller with several modes of operation. Discussion. The proposed model gives a possibility to analyze peculiarities of different control modes used for unmanned aerial vehicle operation. Select the proper values of coefficients that are necessary for optimal and effective interaction between the human and the machine.